2011
DOI: 10.1021/ie101978q
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Hollow Fiber Carbon Membranes from Cellulose Acetate Precursors

Abstract: Hollow fiber carbon membranes (HFCMs) were prepared from deacetylated cellulose acetate precursors using a multidwell carbonization protocol. FTIR, scanning electron microscopy, and thermogravimetric analysis−mass spectrometry were employed to characterize the HFCMs. Gas permeation tests were conducted with single gases (H2, CO2, N2, and CH4) as well as gas mixtures. The single-gas test results indicated that the molecular sieving mechanism dominated in the carbon membrane separation process. The effects and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
4
51
0
Order By: Relevance
“…On the contrary, gas molecules with higher activation energy i.e. N 2 can benefit more from the temperature increase leading to decrease of CO 2 /N 2 selectivity [28]. As the selectivity of all the three gas pairs O 2 /N 2 , H 2 /N 2 and CO 2 / N 2 has decreased with increase in temperature for the PVAc-4A MMMs considered here, therefore activation energy may be the best explanation for this case.…”
Section: Separation Propertiesmentioning
confidence: 69%
See 1 more Smart Citation
“…On the contrary, gas molecules with higher activation energy i.e. N 2 can benefit more from the temperature increase leading to decrease of CO 2 /N 2 selectivity [28]. As the selectivity of all the three gas pairs O 2 /N 2 , H 2 /N 2 and CO 2 / N 2 has decreased with increase in temperature for the PVAc-4A MMMs considered here, therefore activation energy may be the best explanation for this case.…”
Section: Separation Propertiesmentioning
confidence: 69%
“…However the high cost of membrane production and handling issues due to its brittle nature are the challenges that should be addressed to fully exploit its potential for gas separation [25,26]. The work of Memfo research group at NTNU-Norway is worth-mentioning in this regard [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy could be used to investigate the effect of temperature on the degree of permeability increase for different gases and the change in selectivity. The activation energy is higher for gas molecules with larger kinetic diameter, such that N 2 has the highest activation energy and He has the smallest activation energy among the gases investigated in this work. From the Arrhenius‐type equation, higher activation energy results in higher permeation change with temperature .…”
Section: Resultsmentioning
confidence: 87%
“…Xe et al . has analyzed the structure of pyrolyzed cellulose and showed that the thickness of the cellulose‐based carbon membrane was reduced and shrinks from 50 to 30 μm . Conversely, Kiyono et al .…”
Section: Resultsmentioning
confidence: 99%